Assessment of the adherence of radiologists in reporting the ovarian cysts to the 2010 society of radiologists in ultrasound guidelines - Fariba Zarei; Nargessadat Khatamizadeh; Banafsheh Zeinali-Rafsanjani (Journal of Medical Ultrasound, 2023)
Background : The objective of this study was to determine the adherence of radiologists to the guideline of the Society of Radiologists in Ultrasound (SRU)-2010 for the follow-up of ovarian cysts in patients during 2015–2016. Methods : The patients' data, referring for transvaginal and pelvic ultrasonography, suffering from ovarian cyst were assessed in terms of menopause status, cyst size, and type, as well as follow-ups recommended by radiologist to assess the adherence of reports to SRU-2010. Results : Three hundred and sixty-four sonography reports were investigated. Seventy-seven percent of the reports had adhered to SRU-2010, 9.9% and 9.1% had under/overmanagement, and 4.1% was incomplete. 94.2% and 5.8% of cases were in pre/postmenopause status, respectively. The highest adherence belonged to cysts in size <1 cm, 1–3 cm, 5–7 cm. The highest adherence, over/undermanagement, and incomplete reports belonged to corpus luteum, hemorrhagic, dermoid cysts, and nodules without flow. The adherence of sonography reports to SRU-2010 for accidental ovarian cysts was 76.9%. Conclusion: The tendency for overmanagement of simple cysts in premenopausal women and the tendency for undermanagement in simple cysts and in postmenopausal women were higher, respectively. It is expected that more training of the guideline to radiologists will lead to the reduction of unnecessary follow-up, which in turn leads to reduced patient's anxiety and cost of treatment.